Collagen fingerprinting of Caribbean archaeological fish bones: Methodological implications for historical fisheries baselines and anthropogenic change. (September 2022) - Harvey, Virginia L.; LeFebvre, Michelle J.; Sharpe, Ashley E.; Toftgaard, Casper; deFrance, Susan D.; Giovas, Christina M.; Fitzpatrick, Scott M.; Buckley, Michael
Abstract: The Caribbean Sea is the most species-rich sea in the Atlantic, largely due to its vast coral reef systems. However, its high biodiversity and endemism face unprecedented anthropogenic threats, including synergistic modern pressures from overfishing, climate change and bioinvasion. Archaeological data indicate initial human settlement of the Caribbean ∼7000 years before present (yr BP), with regionally variable human impacts on fisheries through time based on standard morphological identification of fish bone. Such studies, however, are challenged by the low taxonomic resolution of archaeological fish bone identifications due to high species diversity and morphological similarity between members of different families or genera. Here, we present collagen fingerprinting (Zooarchaeology by Mass Spectrometry; ZooMS) as a method to overcome this challenge, applying it to 1000 archaeological bone specimens identified morphologically as ray-finned fish (superclass Actinopterygii) from 13 circum-Caribbean sites spanning ca. 3150–300 yr BP (years before present). The method successfully identified collagen-containing samples (n = 720) to family (21%), genus (57%), and species (13%) level. Of the 209 samples that were morphologically identified below superclass, collagen fingerprinting verified the taxonomic identity of 94% of these, but also refined the identifications to a lower [more precise] taxon in 45% of cases. The remaining 6% of morphological identifications were found to be incorrectly assigned. This study represents the largest application of ZooMS to archaeological fish bones to date and advances future research through the identification of up to 20 collagen biomarkers for 45 taxa in 10 families and 2 orders. The results indicate that refinement of ZooMS archaeological fish identifications in this study is limited not by the quality of the preserved collagen but by the extent of the available modern collagen reference collection. Thus, efforts should be directed towards expanding collagen fingerprint databases in the first instance. Significantly, the high-resolution taxonomic identifications of archaeological bone that ZooMS can offer make ancient fisheries data highly relevant to modern sustainability and conservation efforts in the Caribbean. Additionally, more precise identifications will allow archaeologists to address a variety of questions related to cultural fishing practices and changes in fish stocks through time. This study supports the use of ZooMS as an effective biochemical tool available for mass-taxonomic identification of archaeological fish bone samples spanning century to millennial time scales in the circum-Caribbean. Highlights: Applied ZooMS collagen fingerprinting to 1000 archaeological bone specimens identified morphologically as ray-finned fish. Successfully identified the majority of collagen-containing samples to at least genus level. Identification of up to 20 collagen biomarkers for 45 taxa in 10 families and 2 orders. Results indicate that ZooMS most limited by extent of available modern collagen reference spectra.